Insert x + 3 instead of x into the equation of the function f(x):
f(x) = 3 - 6x²
f(x + 3) = 3 - 6(x + 3)²
use (a + b)² = a² + 2ab + b²
= 3 - 6(x² + 2(x)(3) + 3²) = 3 - 6(x² + 6x + 9)
use distributive property
= 3 + (-6)(x²) + (-6)(6x) + (-6)(9) = 3 - 6x² - 36x - 54
combine like terms
= -6x² - 36x - 51
<h3>Answer: f(x + 3) = -6x² - 36x - 51</h3>
Answer
i don't think people wanna do it
Step-by-step explanation:
Answer:
(4x + 12 ) - ( -8 ) =
4x + 20
Explanation:
Just add them up and form a equation ( this is for the second one )
Answer:
C. It increases by a factor of 110
Step-by-step explanation:
For Plato